Manajemen Sarana dan Prasarana Pendidikan di TK Islam Terpadu Bunayya 7 - Fauziah Nasution; Masdeani Dasopang; Tiara Winanda; Rahma Yani; Mastianur Daulay (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to determine the management of educational facilities and infrastructure in the Integrated Islamic Kindergarten Bunayya 7. This research method uses a qualitative approach. The data used from the results of interviews. The results of this study indicate that Bunayya 7 Islamic Integrated Kindergarten is a private school with an “A” accreditation. Not all teachers can apply moral learning in accordance with the demands of the curriculum and the tasks they carry out. Keywords: Teachers, Learning, and Morals